Determinación de dosis de enzimas y tiempos óptimos de hidrólisis para mejorar la digestibilidad de las proteínas obtenidas de residuos de pescado - Lavid Navarrete, Evelyn Consuelo (2019)
The aim of this research was to evaluate the digestibility of fishery residues that have undergone enzymatic hydrolysis processes. A commercial protease obtained by controlled fermentation of a strain of Bacillus spp. Crude residues of commercial value were used such as: viscera, head, tail, discard fish and the liquid from the fish cooking exudate which is a waste with no commercial value not used in the fishing industry, applying the 60/40 ratio respectively. It was analyzed by a completely randomized design with factorial arrangement A x B + 1 and Dunnett was used to determine significance, with factor A being an enzyme dose at levels 20, 35 and 50 ppm, hydrolysis times factor B with 120 and 180 min. Quality control analyzes were performed on raw materials and finished products, digestibility was determined in percentages using the in vitro digestibility method with diluted pepsin A.O.A.C., modified Torry. Giving as a result for digestibility that all the treatments showed P <0.05 against the control being the treatment T6 of 50 ppm enzyme and 180 min with greater degree of digestibility. Significance of factor A and the interaction of factors on histamine was evidenced, with the T1 treatment of 20 ppm enzyme and 120 min being the best behavior. The factors and their interaction showed significance on pH and salt. Therefore, to obtain greater digestibility, fish residues must be hydrolyzed for a period of 180 min with an enzyme dose of 50 ppm.